LARA, F., DECKERS, J. (eds.). (2023). Ethics of Artificial Intelligence. Cham: Springer (The International Library of Ethics, Law and Technology, vol. 41). https://doi.org/10.1007/978-3-031-48135-2 - Gamboa Dennis, Robert (Daimon Revista Internacional de Filosofia, 2025)
Reseña de LARA, F., DECKERS, J. (eds.). (2023). Ethics of Artificial Intelligence. Cham: Springer (The International Library of Ethics, Law and Technology, vol. 41). https://doi.org/10.1007/978-3-031-48135-2